Comprensión lectora y logros de aprendizaje en el área de comunicación en estudiantes del primer grado de secundaria de la institución educativa N° 60080, Caballococha 2024 - Ramon Davila, Maria Mercedes Mery Luz (2025)
The study included 154 first-grade secondary school students from Entity No. 60080 in the city of Caballococha to associate reading comprehension and learning achievements in communication - 2024. Reading comprehension tests were administered, and assessment records were used to collect data for the research. Statistics were performed using the Spearman package of SPSS software, finding a high positive correlation (0.752, p = 0.000), confirming that greater reading comprehension contributes to greater learning achievements.